Non-Reflex Defense Mechanisms of Upper Airway Mucosa: Possible Clinical Application - Pedan, H; Janosova, V; Hajtman, A; Calkovsky, V (Physiological research, 2020)
The sinonasal mucosa has an essential role in defense mechanisms of the upper respiratory tract. The innate immune system presents the primary defense against noxious microorganisms followed by induction of the adaptive immune mechanisms as a consequence of the presence of pathogens. This well-known activation of adaptive immune system in response to presence of the antigen on mucosal surfaces is now broadly applicated in vaccinology research. Prevention of infectious diseases belongs to substantial challenges in maintaining the population health. Non-invasive, easily applicable mucosal vaccination purposes various research opportunities that could be usable in daily practice. However, the existence of multiple limitations such as rapid clearance of vaccine from nasal mucosa by means of mucociliary transport represents a great challenge in development of safe and efficient vaccines. Here we give an updated view on nasal functions with focus on nasal mucosal immunity and its potential application in vaccination in nearly future.
Keywords: Immunity, Mucosal; Animals; Nasal Mucosa; Trachea; respirační sliznice; lidé; Respiratory Mucosa; Administration, Intranasal; zvířata; Laryngeal Mucosa; sliznice hrtanu; slizniční imunita; vakcíny; trachea; aplikace intranazální; nosní sliznice; Vaccines; Humans